EVALI as a disease of the 21st century - Tleubayeva Akmaral; Kakimova Akbota; Ospanova Dilyara; Rakhman Madina; Shyngysbayeva Ayzere; Turganbek Zhamila; Kumar A.B. (Theoretical Hypotheses and Empirical Results, 2023)
Materials and methods We reviewed the literature to document the epidemiology, pathogenesis and risk factors, diagnosis, clinical presentation, evaluation, and treatment of EVALI. Then we prepared a questionnaire in Google forms and sent a link to this questionnaire. As a result, 976 people from the city of Almaty completed a survey, and reports and statistical analysis were prepared based on their data. Results Use of an electronic cigarette (“vaping”) or smoking 90 days before the onset of symptoms was reported by 455 of the 976 respondents. Of the 455 people, 209 were women (45.9%), 246 (54.1%) were men. By age, women under 20 years old - 71, from 20 to 30 years old - 86, from 30 years old - 52 people, and men under 20 years old - 77 cases, from 20 to 30 years old - 98 cases, from 30 years old - 71 cases. Respiratory syndrome (including cough, chest pain, shortness of breath) was reported in 388 people (85.2%). 75% of 341 people reported constitutional symptoms (including weight loss, fever, chills), and 67% (305) had gastrointestinal symptoms (including nausea, vomiting, diarrhea, abdominal pain). Of 388 people with respiratory syndromes, 323 people indicated shortness of breath and cough, chest pain in 52% (202), pleuritic chest pain in 36% (139), hemoptysis - 8% (31). conclusions EVALI is a serious lung disease with public health implications. Diagnostic evaluation of patients with suspected EVALI continues to focus on ruling out alternative and concomitant diagnoses, as EVALI remains a diagnosis of exclusion. This should often be done in conjunction with pulmonary specialists familiar with the disease. Chest imaging is relatively sensitive for EVALI, but results are nonspecific. Bronchoscopy is most useful in ruling out other diagnoses. All patients diagnosed with EVALI should be instructed to avoid using e-cigarettes or other vaping products in the future. Outpatient follow-up with a pulmonologist should be considered as little is known about the long-term effects of this disease.